Perancangan Tongkat Untuk Tunanetra Menggunakan Sensor Ultrasonik Dan Sensor Water Level - Jojor Mei; Alex Surapati; Hendy Santosa (MAJALAH TEKNIK SIMES, 2021)
Abstract Blind people only rely on their sense of hearing because they have a high hearing comprehension. One of the ways that blind people use to walk is like using a stick. But sometimes it is still difficult if you encounter a road surface with a hole so that not a few of the blind people often fall into the hole. Blind people also have difficulty if they encounter uneven road surfaces or flooded roads. From this, the design of the stick was made as a walker for the blind with audio and vibration output. The design of this tool uses the HC-SR04 ultrasonic sensor as detecting objects in front of the user and knowing whether a road has a hole or not. This design also uses a water level sensor to determine whether the road is inundated by water or not, especially on the hollow road. Then the design output of this tool is in the form of audio connected to the earphones and vibrations from the DC motor. The distance detected by the sensor for obstructions is at 100 cm, for potholes when 10-15 cm and for stagnant water when> 50%. If you want to stop using the stick, just push the switch on the stick again. The accuracy level of the HC-SR04 ultrasonic sensor is very good, seen from the error calculation that has been done where the largest error value is obtained at a distance of 10 cm and 20 cm with an error percentage of 0.43% and 0.67%. Furthermore, the smallest error value is obtained at a distance of 30 cm with an error percentage of 0.04%. It can be seen that the ultrasonic sensor works well with an error percentage of0.27%.